Complete genome sequence of Helicobacter pylori B128 7.13 and a single‐step method for the generation of unmarked mutations. Issue 4 (7th May 2019) - Dawson, Emma M.; Dunne, Karl A.; Richardson, Emily J.; Praszkier, Judyta; Alfawaz, Dana; Woelfel, Simon; De Paoli, Amanda; Chaudhry, Hassan; Henderson, Ian R.; Ferrero, Richard L.; Rossiter, Amanda E.
Abstract: Background: Helicobacter pylori represents an interesting model of bacterial pathogenesis given that most infections are asymptomatic, while a minority of infections cause severe gastric disease. H pylori strain B128 7.13 is used extensively to understand H pylori pathophysiology. Due to extensive restriction‐modification systems, the fact that only some H pylori strains are naturally transformable, the inability of common plasmid and transposon vectors to replicate in this bacterium, as well as the limited number of antibiotic cassettes that are functional in H pylori, there are relatively few genetic tools for the mutagenesis of this bacterium. Materials and Methods: Here, we use PacBio and Illumina sequencing to reveal the complete genome sequence of H pylori B128 7.13. Furthermore, we describe a system to generate markerless and scarless mutations on the H pylori chromosome using the counter‐selection marker, galactokinase from Escherichia coli . Results: We show that this mutagenesis strategy can be used to generate in‐frame insertions, gene deletions, and multiple independent mutations in B128 7.13. Using the closed genome as a reference, we also report the absence of second site chromosomal mutations and/or rearrangements in our mutagenized strains. We compare the genome sequence of H pylori B128 7.13 with a closely related strain, H pylori B8, and reveal one notable region of difference, which is a 1430 bp insertion encoding a H pylori‐ specific DUF874 family protein of unknown function. Conclusions: This article reports the closed genome of the important H pylori B128 7.13 strain and a mutagenesis method that can be adopted by researchers as an alternative strategy to generate isogenic mutants of H pylori in order to further our understanding of this bacterium.